Inpatient referrals to consultation-liaison psychiatry at a tertiary hospital in South Africa - Torline, John Ross (Department of Psychiatry and Mental Health, 2017)
Introduction. Consultation-liaison psychiatry is the subspeciality that provides for the psychiatric assessment and management of patients in a hospital setting, serving as an interface between psychiatry and other medical disciplines. This study aimed to provide an analysis of the Consultation-liaison psychiatry service at Groote Schuur Hospital. It was hypothesised that the hospital has a large burden of psychiatric illness amongst inpatients with unique characteristics and high rates of referrals related to HIV, alcohol and methamphetamine use. Methods. A retrospective review was performed of all inpatients referred for psychiatric consultation from other departments over a period of thirteen months. Patients referred by the emergency medical and surgical departments were excluded from this study, as they are seen by the department of emergency psychiatry. Results. A total of 452 patients (males n=174; females n=278) between the ages of 12 and 90 years were consulted, with the majority of the patients (82%, n=360) belonging to the age group of 18 to 59 years (mean age of 37 years). The referral rate to Consultation-liaison psychiatry was 0.95% (when combined with emergency psychiatry referrals the combined referral rate was 4.7%). Most referrals were from the department of medicine (56%, n=252), with the highest number of medical subspeciality referrals from neurology (6%, n=29). Request of a general review (69%) of current psychiatric symptoms (87%) occurred most frequently. The most common symptoms noted by the referring non-psychiatrist were mood symptoms (n=159; 36%), followed by suicidal behaviour (23%, n=102) and behavioural problems (21%, n=94). The mean number of psychiatric diagnoses following assessment was one (SD 1; 0:5), and most patients were assigned a definitive diagnosis (78%, n=342). Alcohol use disorder was diagnosed in 9% (n=41). Methamphetamine use was identified in 5% (n=22) of patients, with the majority being diagnosed with methamphetamine abuse. The use of other substances was identified in 9% (n=38). The HIV status was confirmed positive in 16% (n=70), with the majority of this group being female (67%). Most subjects had psychosocial and environmental problems (55%, n=249). Registrars performed a mean number of one consultation and the majority of patients were seen within 24 hours of the referral. Medication was initiated in 31% (n=139) of cases. The majority (65%, n=292) of patients were discharged from psychiatric care, and 14% (n=61) required admission to an inpatient psychiatric unit. Conclusion. The combined referral rate (consultation-liaison and emergency psychiatry) compares favourably to that of high-income countries, and is higher than any other published studies of this nature in low-income and middle-income countries. There was no substantial agreement between psychiatrist and non-psychiatrist diagnoses. As expected, mood disorders were the most common diagnoses, with only fair agreement between psychiatrist and non-psychiatrist clinicians. A high proportion of referred patients were substance users, but methamphetamine rates were lower than expected and the rate of HIV was higher than anticipated. The results presented here may facilitate improvements in the practice of Consultation-liaison psychiatry.